2018
DOI: 10.1155/2018/2047896
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Wound Healing Activity of the Crude Extract of Leaves of Acanthus polystachyus Delile (Acanthaceae)

Abstract: Background Medicinal plants play indispensable roles to treat various ailments. Acanthus polystachyus is one of the medicinal plants used traditionally for treatment of wounds. However, there were no scientific reports documented so far on the wound healing activities of this plant. Thus, the present study provides a scientific evaluation for the wound healing potential of the crude extract of A. polystachyus leaves. Methods The crude extraction was carried out using 80% methanol. The crude extract was prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 19 publications
4
65
0
1
Order By: Relevance
“…However, any disturbance in the deposition and maturation of the collagen fibers may reduce wound strength, and cause wound dehiscence [26] . Similar to that of our finding, crude extract of Acanthus polystachyus Delile was found to enhance the rate of wound retraction of excisional and incisional wounds in normal Swiss albino mice [27] . Another study who used Copaifera pauper extrac in diabetic Swiss Webster mice, revealed a better wound closure, and higher level of collagen deposition compared to that of collagenase treated wounds [28] .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, any disturbance in the deposition and maturation of the collagen fibers may reduce wound strength, and cause wound dehiscence [26] . Similar to that of our finding, crude extract of Acanthus polystachyus Delile was found to enhance the rate of wound retraction of excisional and incisional wounds in normal Swiss albino mice [27] . Another study who used Copaifera pauper extrac in diabetic Swiss Webster mice, revealed a better wound closure, and higher level of collagen deposition compared to that of collagenase treated wounds [28] .…”
Section: Resultssupporting
confidence: 91%
“…Dewangan, Bais [39] reported a higher regeneration rate with a thinner epidermis in wounds that had been treated with different concentrations of the Solanum xanthocarpum Schrad and Wendl extract. The excisional and incisional wounds, which had been treated with crude extract of Acanthus polystachyus Delile were found to have a faster reepithelialization rate compare to untreated-wounds in Swiss albino mice [27] . Consistence with our finding, Copaifera pauper extract were reported to improve reepithelialization processes in diabetic Swiss Webster mice compared to that of collagenase treated wounds [28] .…”
Section: Resultsmentioning
confidence: 92%
“…There is no pharmacological evidence in current literature on the use of Acanthus polystachyus, Keetia guienzii and Rhychosia elegans. However, available literature suggests that Acanthus polystachyus is traditionally indicated for malaria [11], and in the management of scorpion bites [12] while Rhynchosia elegans has been reported to be traditionally used in ethnoveterinary practice in managing backleg, anthrax, amoebiasis, malaria, cold and fever [11,170]. To the best of our knowledge, this study provides the first report of the medicinal use of Keetia guenzii.…”
Section: Pharmacological Reports On the Medicinal Plants Documented Imentioning
confidence: 99%
“…The percent wound healing of S. incanum (81%) was also far better in comparison to vehicle treated group (23%). These results can be supported by the fact that faster closure of wound indicated the better efficacy of medication (Demilew et al, 2018). Previous studies reveals that the active agents in herbal extracts such as triterpenes, alkaloids, flavonoids, tannins, saponins, anthraquinones, and secondary metabolites have role in promoting the healing process (Chaudhari and Mengi, 2006).…”
Section: Discussionmentioning
confidence: 87%